CHRONIC SPORTS BETTING AND SOCIAL WELL-BEING IN YOUNG ADULTS: ROLES OF EMOTIONAL INTELLIGENCE AND SELF-REGULATION - Oyekwe, Somto Juliet; Ugwu, Fabian O. (African Journal of Social and Behavioural Sciences, 2025)
Online cross-sectional data were collected from a total of 300 undergraduate students sampled from a federal university in the Southeastern region of Nigeria to investigate the moderating roles of emotional intelligence and self-regulation in the relationship between chronic sports betting and social well-being. Contrary to our speculation, the results of the moderated regression analysis indicated that chronic sports betting was significantly and positively related to social well-being. Emotional intelligence and self-regulation significantly and positively impacted on social well-being. The results of the study also showed that emotional intelligence and selfregulation moderated the impact of chronic sports betting on social well-being. These findings suggest that context is important when the impact of chronic sports betting is discussed. Besides, emotional intelligence and self-regulation are effective intervention techniques that can improve social well-being despite chronic sports betting.